In situ BCL2 expression is an independent prognostic factor in HIV‐associated DLBCL, a LYMPHOVIR cohort study. (29th August 2019) - Philippe, Laure; Lancar, Remi; Laurent, Camille; Algarte‐Genin, Michele; Chassagne‐Clément, Catherine; Fabiani, Bettina; Pierre Chenard, Marie; Lazure, Thierry; Parrens, Marie; Charlotte, Frederic; Delattre, Claire; Gibault, Laure; et al.
Summary: The prognostic value of cell of origin (COO) classification and BCL2 expression is not well established in diffuse large B‐cell lymphoma (DLBCL) patients with human immunodeficiency virus (HIV) infection in the recent era. Phenotypic patterns were determined by immunohistochemistry (IHC) of pathological samples from patients with HIV‐associated DLBCL prospectively enrolled in the French AIDS and Viral Hepatitis CO16 Lymphovir cohort between 2008 and 2015. Molecular subgroup classification into germinal centre B‐cell (GCB) and non‐GCB subtypes was determined using the Hans algorithm. Among 52 samples of systemic DLBCL subjected to centralized pathological analysis, 25 of the 42 tested for BCL2 expression were positive. Samples were further classified into GCB ( n  = 19) and non‐GCB ( n  = 16) subtypes and 17 remained unclassified. In multivariable analysis, BCL2 expression was an independent pejorative prognostic biomarker [4‐year progression‐free survival (PFS): 52% for BCL2 + vs. 88% for BCL2 −, P  = 0·02] and tended to reduce 4‐year overall survival (OS) (63% for BCL2 + vs. 88% for BCL2 −, P  = 0·06). The difference between CGB and non‐GCB subtypes on PFS and OS did not reach significance (4‐year PFS: 79% for GCB vs. 53% for non‐GCB, P  = 0·24 and 4‐year OS: 78% for GCB vs. 69% for non‐GCB, P  = 0·34). BCL2 expression determined by IHC is an independent pejorative prognostic biomarker in HIV‐associated DLBCL in the recent era. This supports the investigation of new therapeutic strategies in patients with BCL2 expression.